Об’єкти історико-культурної спадщини України в умовах війни: урбіцид та його наслідки - Бучко, Жанна; Стецюк, Андрій (Чернівці: Чернівецький національний університет, 2023)
Метою статті стало узагальнення наслідків військового урбіциду для об’єктів історико-культурної спадщини України в розрізі регіонів і вирішення таких завдань, як аналіз концепту-альних підходів до вивчення питання впливу військового урбіциду на історико-культурну спад- щину регіонів України. До аналізу поточної ситуації спонукали звернутися прямі чи опосеред-ковані деструктивні наслідки для об’єктів культурно-історичної спадщини, втрати містами їх ідентичності. У статті розглянуто концепцію урбіциду як специфічну насильницьку політику проти міст, що має місце упродовж останнього року, з часу початку повномасштабної російсь-ко-української війни. Досліджено регіональні особливості зафіксованих злочинів на території України щодо істо-рико-культурної спадщини. З’ясовано, що за рік повномасштабної російсько-української війни зазнали руйнувань та пошкоджень 569 об’єктів культурної спадщини. Найбільша кількість таких випадків характерна для Донецької, Харківської та Київської областей. Зруйновано та пошкоджено ряд музеїв, колекції деяких знищені, розграбовані, вивезені на непідконтрольну Україні територію. Зруйновано та пошкоджено 170 пам’яток національного та місцевого значен- ня, 146 об’єктів цінної історичної забудови та культурної спадщини, а також 58 меморіальних пам’ятників та творів мистецтва.
Historical and Cultural Heritage Objects of Ukraine in the Conditions of War: Urbicide and Its Consequences
The purpose of the article was to generalize the consequences of military urbicide for objects of historical and cultural heritage of Ukraine by region and to solve such tasks as the analysis of concep-tual approaches to the study of the impact of military urbicide on the historical and cultural heritage of the regions of Ukraine. The analysis of the current situation was motivated by the direct or indirect destructive consequences for objects of cultural and historical heritage, the loss of their identity by cities. The article examines the concept of urbicide as a specific violent policy against cities that has been taking place over the last year, since the beginning of the full-scale Russian-Ukrainian war. February 24, 2022 was the beginning of mass military urbicide in Ukraine. The occupation of cities and long-term military actions caused a powerful and multidimensional impact on all processes of the life of the civilian population, communication opportunities, led to numerous victims and the destruc-tion of entire settlements, residential areas, and individual buildings. The regional features of recorded crimes on the territory of Ukraine regarding the historical and cultural heritage were studied. It was found that during the year of the full-scale Russian-Ukrainian war, 569 objects of cultural heritage were destroyed and damaged. The largest number of such cases is characteristic of Donetsk, Kharkiv and Kyiv regions. A number of museums were destroyed and damaged, the collections of some were destroyed, looted, and taken to the territory not controlled by Ukraine. 170 monuments of national and local importance, 146 objects of valuable historical buildings and cultural heritage, as well as 58 memorial monuments and works of art were destroyed and dam-aged.
Keywords: історико-культурна спадщина; урбіцид; російсько-українська війна; пам’ятка культури; музей; туризм; historical and cultural heritage; urbicide; Russian-Ukrainian war; cultural monument; museum; tourism